Work-Life Balance and Organizational Commitment on Employee Performance: The Mediation Role of Job Satisfaction - Frisca Egidia Aviptasari; Vini Wiratno Putri (Management Analysis Journal, 2024)
This research aims to examine the influence of work-life balance and organizational commitment on employee performance through job satisfaction. The population in this study were permanent employees of the sanding department at PT. Sandang Asia Maju Abadi. The sampling technique used in this research was a purposive sampling technique using a saturated sampling technique with a sample size of 147 employees. The data analysis method uses descriptive statistical tests via SmartPLS 4.0 data processing software. The research results show that there is a positive and significant influence of work-life balance on employee performance. Organizational commitment has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. Also, job satisfaction mediates the influence of work-life balance and organizational commitment on employee performance. Future research can use other variables as mediating variables for different research objects to obtain more generalized research results. Company management can improve employee performance by holding training and development sessions as well as more regular work evaluations for employees. Employees are expected to regularly participate in work evaluations and make good use of their time after work.